2011
DOI: 10.1111/j.1752-1688.2011.00587.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Performance of Statistical Models in Forecasting Monthly Total Dissolved Solids in the Rio Grande1

Abstract: Abudu, S., J.P. King, Z. Sheng, 2011. Comparison of the Performance of Statistical Models in Forecasting Monthly Total Dissolved Solids in the Rio Grande. Journal of the American Water Resources Association (JAWRA) 48(1): 10‐23. DOI: 10.1111/j.1752‐1688.2011.00587.x Abstract:  This paper presents the application of autoregressive integrated moving average (ARIMA), transfer function‐noise (TFN), and artificial neural networks (ANNs) modeling approaches in forecasting monthly total dissolved solids (TDS) of wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
36
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 30 publications
0
36
1
1
Order By: Relevance
“…ANN model provides a powerful tool for modeling the complex nonlinear relationship between inputs and outputs [26]. It has been demonstrated that ANN model can provide better forecasting accuracy than statistical-based methods [27].…”
Section: Artificial Neural Network Modelmentioning
confidence: 99%
“…ANN model provides a powerful tool for modeling the complex nonlinear relationship between inputs and outputs [26]. It has been demonstrated that ANN model can provide better forecasting accuracy than statistical-based methods [27].…”
Section: Artificial Neural Network Modelmentioning
confidence: 99%
“…The northern Xinjiang is one of the areas exhibiting frequent snowmelt flood disasters in Xinjiang [5]. Therefore, the assessment of maximum snowpack volumes plays an important role in regional water resource management and flood prevention [6][7][8].The snow water equivalent (SWE), as an important variable in the earth system, reflects the amount of water resources in the form of snow. The SWE is also the main factor influencing river runoff, the regional water resources supply, and flood safety during the snowmelt period.…”
mentioning
confidence: 99%
“…The SWE is also the main factor influencing river runoff, the regional water resources supply, and flood safety during the snowmelt period. Therefore, accurate acquisition of the snow water equivalent is of great significance for studies on hydrology, meteorology, the water cycle, and global climate change [8,9]. However, accurate estimation of the watershed SWE is the major problem to be solved in the study of mountain hydrology [10].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Como aplicações, pode-se citar o controle de cheias, gerenciamento de irrigação e operação de reservatórios de abastecimento de água, bem como aspectos legais e institucionais relacionados ao gerenciamento e planejamento dos recursos hídricos [54].…”
Section: Vazão Natural Afluente: Definiçãounclassified